Edukasi Rasionalisasi Penggunaan Antibiotik pada Kasus Pneumonia di Masyarakat - Syafina, Ikhfana (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2025)
Pneumonia remains a major public health concern, often treated improperly with antibiotics. This study aims to explore the impact of community-based education on the rational use of antibiotics for pneumonia. Using a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and focus group discussions. The findings reveal that most participants initially misunderstood antibiotic functions and frequently used them without prescriptions. After interactive educational sessions, participants showed improved understanding and expressed a strong commitment to responsible antibiotic use. The involvement of local health workers and community leaders played a vital role in enhancing program effectiveness. This study highlights the importance of structured, community-oriented education in promoting rational antibiotic practices and preventing antimicrobial resistance. The success of this initiative suggests its potential to be scaled up and replicated in other communities facing similar health behavior challenges.